Maternal anemia and low birth weight in a community development block of Purba Bardhaman, West Bengal: a retrospective cohort analysis - Biswas, Puspendu; Samsuzzaman, M.; Chakraborty, Amitava; Das, Dilip Kumar (International Journal Of Community Medicine And Public Health, 2019)
Background: Being both highly prevalent public health problems in India, anemia in pregnancy (AIP) is hypothesized as a potential risk factor for low birth weight (LBW) baby as pregnancy outcome. In this context, this study was conducted among pregnant mothers registered in last 2 years under Bhatar block of Purba Bardhaman district, West Bengal. Objectives of this study were to assess the relationship of LBW babies with maternal anemia in antenatal period and also with background characteristics and pregnancy related factors. Methods: A retrospective cohort analysis was conducted among postnatal mothers who were registered during their pregnancy in sub-centers of this block during a reference period from April’15th - March’17th. The study subjects were identified from the records of each sub-centre and further categorized into two groups: Exposed (anemic) - Hb <11 gm% in any antenatal visits and Non-exposed(non-anemic) - Hb ≥11 gm% in all antenatal visits. Sample size of 988 for each group was calculated. From each sub-centre’s antenatal record 26 subjects for each group were selected by simple random sampling. Data collected with predesigned pretested schedule and data analyzed using Microsoft Excel and SPSS 20. Logistic regression was performed to establish association. Results: Overall incidence of LBW was 8.1%; in anemic, non-anemic group incidence were 10.5%, 5.7% respectively. AIP had relative risk 1.85 (1.36-2.54) over LBW. On multivariable logistic regression, LBW was significantly associated with AIP (2.11, 1.51-2.95), multi-parity (0.63, 0.44-0.9), inadequate ANC visits (2.7, 1.75-4.15) and female gender (1.64, 1.19-2.27). Conclusions: Anemia in pregnancy significantly increases risks of LBW which also strongly associated with female new-born, primi-parity, and incomplete ANC visits.